Cognitive Biases as Boosters - Using Cognitive Biases to Improve Communication Recall for Emmi Jogurtpur - Matthias Fuchs; Christian Omlin; Stefan Naef; Thomas Steiner; Etienne Schumpf; Johanna Franziska Gollnhofer (Marketing Review St.Gallen, 2022)
Only one in three Swiss brands strategically uses insights from consumer psychology research when developing new marketing communication. However, if done in a structured and strategic way, applying these insights can boost a brand's marketing performance. We present the successful application of insights from consumer psychology research to Emmi Jogurtpur. We show how it can be done and how successful it can be for brands.
Keywords: 650